Synthesis, structure–activity relationship and molecular docking of 3-oxoaurones and 3-thioaurones as acetylcholinesterase and butyrylcholinesterase inhibitors. Issue 1 (1st January 2017) - Mughal, Ehsan Ullah; Sadiq, Amina; Murtaza, Shahzad; Rafique, Hummera; Zafar, Muhammad Naveed; Riaz, Tauqeer; Khan, Bilal Ahmad; Hameed, Abdul; Khan, Khalid Mohammed
Graphical abstract: Abstract: The present study describes efficient and facile syntheses of varyingly substituted 3-thioaurones from the corresponding 3-oxoaurones using Lawesson's reagent and phosphorous pentasulfide. In comparison, the latter methodology was proved more convenient, giving higher yields and required short and simple methodology. The structures of synthetic compounds were unambiguously elucidated by IR, MS and NMR spectroscopy. All synthetic compounds were screened for their inhibitory potential against in vitro acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. Molecular docking studies were also performed in order to examine their binding interactions with AChE and BChE human proteins. Both studies revealed that some of these compounds were found to be good inhibitors against AChE and BChE.